Effect of Supllementary Safflower Oil (Carthamus tinctorius)On Some Blood Paramerers of Common Carp (Cyprinus carpio L) - Alobadiy, Taghreed Sadeq; Alakreem, Amer Abd (Journal of Kerbala for Agricultural Sciences, 2018)
The experiment carried out in fishes labrotary in the college of agriculture /university of Baghdad for 75 days ,of common carp Cyprinus carpio distributed randomly with average weight 33.02gm fish on 15glass tan with dimensions of (60x40x40cm) and on five treatments experience in three replicates (7 fishes for glass),were fed on manufactured in labrotary with protein content between 23.62and 26.50 % and energy about 3021.45 and 3073.75 calorie/ kgm. The Results of the statistical analysis of of cholesterol showed no significant differences between treatment T3 (139.5) and T1, T2 and T4, which reached 146.2, 144.6 and 131.75 mg / dl respectively .The result cholesterol level checking decrease of triglycerides with increase the level of safflower oil in diet , it was the highest value for the T1 (210.15) mg/dl and the lowest value for T5it was 100.85 mg/dl. and no significant difference (p<0.01)for high density lipoproteins but the highest value was for T5 (49.10 mg/dl), and the result of low density lipoprotein show increase with increase of safflower oil it was the lowest value forT5(30.85, 31.10 mg/dl) We inference from this study the possibility of adding safflower oil, helping them control the cholesterol levels and lipoproteins in the blood of common carp.